A Systematic Examination of Digital Technology Integration in English Language Teaching at Vocational High Schools: Challenges and Opportunities - Rahmaniar; Zulkifli Surahmat; Emelia Fitri Limchio Sinaga (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
The use of various technologies in vocational high schools in response to the need for graduates to have digital and English skills have changed English instruction even more. This study attempts to analyze the issues and the possibilities that both educators and learners face as they use digital technologies in English teaching. This study is limited to five English teachers in vocational high schools in West Sulawesi, Indonesia. This case study employed qualitative methodology through in-depth interviews and ATLAS.ti 24 software was used for data analysis. Findings showed that the teachers face several issues including the lack of technology, poor and unreliable internet, limited assistance, and different amounts of digital skills students have. Nevertheless, the study also showed that teachers' use of different digital technologies and more varied methods of teaching English motivated students to become involved and participate in English learning more than they have in the past. In addition to this, more skilled teachers are better able to adapt their material to fit vocational contexts and therefore increase relevancy to students’ future workplace outcomes, as this study has shown. The study adds to the knowledge base by showing that the successful application of digital technologies in vocational English education is not only a question of existing digital technologies and infrastructure, but also of ongoing professional digital pedagogical training and educational organizational support. The authors of the study are suggesting that digital infrastructures are available, that there are ongoing training efforts, and that there is a balanced provision of digital tools and resources for educators. These steps are required to take full advantage of digital technologies for teaching and learning English in vocational secondary education.